ادارة التدفقات النقدية في ضوء ثنائية ملاءة/مردودية - محمد عبد النور كيسوم; ايمان- سردوك (My University, 2021)
The purpose of maximizing profitability comes on top of the goals that the organization seeks to getit in order to continuity and growth, in turn, this leadsto the growing size of the risks associated with them, and this is reflected negatively to achieve results. Between this and that, cash flow management come in order to equilibrate. Between highe rprofitability levels, and reduce the size of the associated risks,through management of the elementsrequirement in working capital, andfinancedeficit in the best possible condition, in addition to maintain optimum ................................................. إن غرض تعظيم الربحية يأتي على رأس الأهداف التي تسعى إليها المنظمة للحصول عليها من أجل الاستمرارية والنمو، وهذا بدوره يؤدي إلى تزايد حجم المخاطر المرتبطة بها معهم، وهذا ينعكس سلباً على تحقيق النتائج. وبين هذا وذاك، تأتي إدارة التدفق النقدي من أجل التوازن. بين مستويات ربحية عالية، وتقليص حجم المخاطر المرتبطة بها، من خلال إدارة مقومات رأس المال العامل، والعجز التمويلي بأفضل صورة ممكنة شرط ذلك، بالإضافة إلى الحفاظ على الحجم الأمثل للنقدية، حيث لا يمكن إبقاء الفوائض تؤدي إلى إخفائها التكاليف على شكل فرص ضائعة..